Die Frageleiter Als Die Medium Der Sprechfertigkeit Des Deutschunterrichts An Der Sma Klasse XI (ein Vorschlag) - ODICE, OKTAVIA (LATERNE, 2013)
In the teaching and learning process, the medium is any important component in the learning process of students. A teacher should be made creation, preparation and development of teaching media. Media must need a good plan to be effective to use. The medium of the question ladder is a medium that is collected when you register a few questions. The questions are structured so that they are from the simple to the most complex questions. The order of these questions are on the classification of the Bloom taxonomy and includes the C1, C2, and C3. The problem of this study is: how is the medium developed and what are the steps in the application of media in teaching German and speaking skills in SMA class XI? The aim of the study is: to describe the development of medium and the steps of the application in the teaching of German in the SMA Class XI. This research method is a bibliography. For this study theories from different sources are collected, referring to the media, the Internet and speaking skills. The steps of development of this medium are: 1) Analyze the needs and characteristics of students; in German class must be the needs dominate the students, there is the competence to KTSP SMA 2006, while the characteristics of the students are usually male and female. The students have already obtained in the class XI semester I. 2) Formulate the learning objectives; the basic competence expresses verbal information in the form of presentation or simple dialogue on the family, 3) Formulate the matter, the matter that will be applied to the family. These are vocabulary, expression, conversation and structure. 4) Arranging the evaluation, the success is the fulfillment of the task and the pronunciation, 5) The media text, the questions are written in each ladder. The question is from the simple to the most complex questions, 6) Validation matter, the matter will discus the matter with benefits consultant. This medium, which has been making the investigator, they would experiment in the teaching process. The teaching of these steps are medium: 1) First activities; teacher motivates the students with the theme, says the learning objectives and makes the associogram, 2) Principal activities; teacher gives students matter to the family. These are vocabulary, expression, conversation and structure. Then apply to the medium of the teacher question ladder and gives students the task, 3) Abschluβ activities, teachers and students repeat the matter. The results of the study are the development of medium of the question ladder, this medium is still theoretical. The future researchers may be experimenting with this medium and creative and interesting ideas. The results of this medium can be used as a new medium, the offer in the learning process, especially German lessons Height help. Keywords: media, the medium of the question ladder, speaking skills.